Translation : the interpretive model - Lederer, Marianne (Taylor and Francis, 2014)
This book, the English version of La traduction aujourd'hui (Hachette 1994), describes the interpretive theory of translation developed at the Paris Ecole Supérieure d'Interprètes et de Traducteurs (ESIT) over the last 35 years. The theory identifies the mental and cognitive processes involved in both oral and written translation: understanding the text, deverbalizing its language, re-expressing sense. For the purposes of translation, languages are a means of transmitting sense, they are not to be translated as such.